BENTUK PERLINDUNGAN HUKUM TERHADAP KONSUMEN AKIBAT IKLAN YANG MENYESATKAN PADA MEDIA CETAK - Tulus Siambaton; Yosua Lorenzo Tarigan (LPPM Universitas HKBP Nommensen, 2020)
This study aims to determine the implementation of legal protection for consumers due to misleading print media advertising against misleading advertisements in print media viewed from Law No. 8 of 1999 on Consumer Protection because, in fact there are still consumers who do not know how the legal protection is due to such misleading advertising. The method used in the writing of this research is the method of library research that collects data by doing library material or secondary data that includes legislation, books, mass media, and other reading related to the writing of this research and field research methods , which is a research process by collecting data related to obtained directly from the field. In this study the collection of data in the form of interviews obtained at the place of pre-determined interviews. From the results of research obtain the form of legal protection that can be done by consumers due to misleading print media advertising is in the form of the Institution Consumer Protection Society (LPKSM) which has the task of one is to assist consumers in fighting for rights, which is based on the The Consumer Protection of Law in protecting consumers other than those officially established by the government, in Chapter IX Article 44 and the accountability of the respective business actors are those responsible for providing compensation for damage, pollution and / or consumer loss resulting from the consumption of goods and / or services produced or traded under Article 7, Article 19 paragraph (1) and Article 20 UUPK (The Consumer Protection of Law).